HUBUNGAN TIPE KEPRIBADIAN DENGAN TINGKAT STRESS MAHASISWA D-III KEBIDANAN STIKes INDRAMAYU TAHUN 2018 - Intan Anggita Sidik (JURNAL KESEHATAN INDRA HUSADA, 2020)
personality typeis divided into 2 extrovert and introvert who has extrovert edpersonality types are good at socializing, Stress is a psychological phenomenonthat is often encountered indaily life, in which every individual must have experienced it low, strandart and high.but the level stress suffered by any person not the same aim of this study to know Relationships Personality Types with levels of stress student D-IV midwife STIKes Indramayu 2018 Analytical method with acrosssectional descriptive study, the sample in the study all students study the D-III program midwife STIKes Indramayu year 2018. Metode total sampling, total of 40 people, the research instrument is a questionnaire, and processed with computer programs.The results showed the majority of personality ektrovert is 26 students (65%) and mild stress levels is 25 students (62,5%). The analysis shows that using spearman rank p = 0.066 and 0.05 significance level. And the correlation coefficient (rs) is equal to - 0.279 means that there is no relationship between personality type with student stress levels.